THE OPINION OF JAMAAH TABLIGH ABOUT MARRIAGE AGE BY UNDANG-UNDANG NUMBER 16 OF 2019 (A Case Study of the Jamaah Tabligh in Deli Serdang District) - Muhammad Fadhil (Sekolah Pascasarjana Universitas Swadaya Gunung Jati, 2023)
This study aims to answer how the opinions and practices of the Jamaah Tabligh in Deli Serdang district about the age of marriage by making Undang-Undang Number 16 of 2019 as the basis for the analysis. This study uses empirical juridical research, and data collection techniques in this study are observation, interviews, and document studies. This study found that there are opinions and practices of the Jamaah Tabligh community in Deli Serdang district in marrying off their children may be done when they reach puberty. The background factor is to avoid adultery and promiscuity. Meanwhile, the minimum age for marriage regulated in the Undang-Undang Number 16 of 2019 for men and women as stipulated in Undang-Undang Number 16 of 2019 concerning amendments to Undang-Undang Number 1 of 1974 concerning Marriage. According to the opinions of the Jamaah Tabligh in Deli Serdang district Stick rules regarding the minimum age limit for marriage stipulated in the law are a form of recommendation, so there is no problem with not following the statutory rules regarding the minimum age limit for marriage when marrying off their children for good purposes.